PEMBELAJARAN MATEMATIKA MATERI PENGUKURAN SATUAN PANJANG MELALUI MEDIA BATIK NUSANTARA - Yenny Widyawati; Ahsanul Huda Susanto; Fitri Lastini; Sri Haryanti; Maftuhah Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study on mathematics learning in the topic of length measurement using Nusantara batik as a medium aims to analyze the use of Nusantara batik in teaching length measurement in third-grade elementary school and to explore students' responses to this medium. This research employed a qualitative approach conducted at SDN 04 Karangsari, involving 12 female students and 10 male students. Data collection methods included observation, interviews, and documentation. Data validity was ensured through source triangulation by combining data from observations, interviews, and documentation to ensure consistency of results. The data analysis technique used was the Miles and Huberman model, which consists of three stages: data reduction, data presentation, and conclusion drawing. The results indicate that the use of Nusantara batik in teaching length measurement not only enhances students' understanding of mathematical concepts but also enriches their learning experience by connecting the subject matter to local culture. Students showed high interest and motivation when learning with batik motifs, as they could see a direct relationship between mathematical concepts and daily life. Furthermore, students were able to better understand measurement concepts through analyzing patterns and designs in batik, which involve comprehension of geometry, transformation, and symmetry.